The Concept of Cause and its Functions According to Al-Amedi - Layla, Layla; Tar, Tar (State Islamic University Datokarama Palu, 2025)
In this research, the concept of cause was discussed. This concept is central in jurisprudential studies. Attempts were made to throw light on the concept and its common literal and jurisprudential aspects. A special part was dedicated to the approach of the author of the book Precision of Principles of Judgements, which is specialized in developing the principles of jurisprudence. The latter effort was made to explain Al-Amedi’s point of view regarding the concept of cause and the relevant Sharia and rational orders and purposes.